The Power of Social Sources on Students’ Well-being in Primary School. The Role of Teachers and Peers in Classroom Positive Emotions and Perceptions of Future School Success - Mara Marini; Irene Stazione; Emanuela Botta; Stefano Livi (Journal of Educational, Cultural and Psychological Studies, 2025)
Abstract